Effect of All-Trans Retinoic Acid (ATRA) against expression of Matrix Metalloproteinase-2 (MMP-2) in model mice (Rattus norvegicus) periodontitis - Soraya, Ilma; Herdiana, Nadya Octoraputri; Hanggoro, Rifan; Widodo, Haris Budi (Universitas Padjadjaran, 2017)
Introduction: Periodontitis is a common chronic inflammatory disease characterised by destruction of the supporting structures of the teeth, generally caused by bacteria Phorphyromonas gingivalis (P.g). Matrix metalloproteinase-2 (MMP-2) is an enzyme that plays an important role in inflammatory conditions. All-trans retinoic acid is a metabolite of vitamin A which plays a role in healing the inflamed tissue and maintain the immune system. The purpose of this study was to determine the effect of ATRA on the expression of MMP-2 in periodontitis models of mouse Rattus norvegicus. Methods: this was a laboratory experimental study using post-test only with control group design. This study used 25 male Wistar mice that was divided into 5 groups. Group 1 is a group of healthy mice, Group 2 is a group of periodontitis induced mice without treatment, Group 3 is a group of periodontitis mice treated with 5 mg/kgBW doses of ATRA, Group 4 is a group of periodontitis mice treated with 10 mg/kgBW doses of ATRA, and Group 5 is a group of periodontitis mice treated with 20 mg/kgBW doses of ATRA. The periodontitis was induced using Phorphyromonas gingivalis bacteria every 3 days for 28 days and followed by administration of ATRA for 7 days. Expression of MMP-2 from gingival tissues and periodontal ligament was obtained by immunohistochemical methods. The results were analyzed using the Shapiro-Wilk Test and Mann-Whitney Test. Results: The results showed there were significant differences in the positive area of MMP-2 and MMP-2 color intensity (p<0.05) between Groups. Conclusion: ATRA dose of 20 mg/kgBW is the most effective dose in inhibiting the expression of MMP-2 in mice models of periodontitis when compared with other doses.